PENCIPTAAN BUKU ESAI FOTOGRAFI PANTAI JATIMALANG UNTUK MENGOPTIMALKAN POTENSI WISATA PURWOREJO - Aminuddin, Muhammad Nur; Bahruddin, Muh; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2015)
Abstract: In the District Regulation No. 4 of 2009 Purworejo About Tourism Potential Determination as Tourist Attractions, Jatimalang beach designated as coastal tourism potential. Explained that the tourism potential of a capital means for the development and improvement of tourism. Because if used optimally tourism potential will have a positive impact on the increasing number of tourists as well as increased revenue. In terms of tourism, Purworejo is still fairly new and is in a developing stage. So to make Purworejo as a tourist destination, tourism potential should be explored optimally. On the basis of the authors set out to create photographic essay book with the theme Jatimalang Beach. Where in this book will show a collection of photos of Beaches Jatimalang and photographs related to the assembled to have grooves that are uniting to give a detailed description of how the state, atmosphere and charm Jatimalang Beach attractions. The study was conducted using qualitative methods, namely observation, interviews and literature studies to conclude the concept of the design process. Through the process of data analysis, found the keyword